Nanomaterials for CO2 Capture from Gas Streams - Francisco Jose Alguacil (Separations, 2023)
Since CO2 is an important component of gas emissions, its removal from gas streams is of the utmost importance to fulfill various environmental requirements. The technologies used to accomplish this removal are based mainly on absorption, as well as adsorption and membrane processing. Among the materials used in the above separation processes, materials in nano forms offer a potential alternative to other commonly used macromaterials. The present work reviews the most recent publications (2023) about CO2 capture using different nanomaterials, and whilst most of these publications were dedicated to investigating the above, several presented data on the separation of CO2 from other gases, namely nitrogen and methane. Furthermore, a number of publications investigated the recyclability of nanomaterials under continuous use, and just three of the references were about computational modeling; all others were experimental papers, and only one reference used a real industrial gas.